Analisis Perhitungan Harga Perolehan Dan Harga Jual Guna Menentukan Pajak Pertambahan Nilai Atas Perubahan Tarif 10% Menjadi 11% - Lazuardy Rinto Admaja; Muhammad Alfa Niam; Rike Selviasari (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research aims to determine the calculation of acquisition price and selling price in order to determine value added tax. The analytical method used in this research is descriptive quantitative. This research data is qualitative and quantitative. Researcher data collection techniques are interviews and documentation. The research variables are acquisition price, selling price, and value added tax. The results of the research show that UD. Meteor in calculating the acquisition price is not correct because it has not added the acquisition cost element. In calculating prices, UD. Meteor is correct because it adds a mark up in its calculations, but it is not correct because it has not added the elements of electricity costs, telephone costs, equipment costs and labor costs. Therefore, the calculations in this study are greater than the UD calculations. Meteor. Based on the results of calculating the acquisition price and selling price in this research, the calculated value added tax is IDR 71,104,945.UD. Meteor should pay more attention to costs such as acquisition costs, electricity costs, telephone costs, equipment costs and labor costs when carrying out business activities, and calculate them properly. Preferably UD. Meteor recalculates the acquisition price and selling price by adding acquisition costs, electricity costs, telephone costs, equipment costs and labor costs. So that the acquisition price and selling price determined are more appropriate.